Proterozoic Sutures in Canada - Gibb, R.; Thomas, M; Mukhopadhyay, M. (Geoscience Canada, 1980)
Summary Geophysicists generally agree that one ormore supercontinents were in motion duringthe Proterozoic. A more controversial issueis whether these supercontinents were attimes internally fragmented into smallercrustal units that subsequently collided andsutured in the manner of Phanerozoicplates. Several sutures or join lines betweencollided continental fragments have beenproposed in the Canadian Shield. These areall of Proterozoic age although severalauthors have suggested that some form ofprimitive plate tectonics was operative in theformation of Archean crust of the Superiorprovince. A wide variety of geological andgeophysical evidence has been advancedin support of the proposed sutures. Viewedcollectively, the evidence makes a convinc-ing argument for plate tectonics in theProterozoic. However, it appears that con-clusive evidence for relative motions bet-ween units of the Shield in this period will beforthcoming only from more precisepaleomagnetic and geochronologic studiesof critical rocks